Physiological field measurements between junior and preadolescent rhythmic sports gymnasts - Douda, H.; Avloniti, A.; Toubekis, A.; Tokmakidis, S. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The purpose of this study was to determine the metabolic demands using field tests during RSG routines on different apparatus between junior and preadolescent gymnasts. The findings revealed that RSG is a demanding discipline and all routines have similar metabolic demands despite of the material regulations on each apparatus. The high aerobic and anaerobic values obtained during both the competitive routines and the laboratory measurements indicate the important role of these metabolic mechanisms. Therefore, for a better planning of training the RSG coach should take into consideration that the athletes require anaerobic capability as well as aerobic capability in order to satisfy the energy demands and replace the high energy phosphate sources required during the competitive routines.